Cytomictic Anomalous Male Meiosis and 2n Pollen Grain Formation in Mertensia echioides Benth. (Boraginaceae) from Kashmir Himalaya - Reyaz Ahmad Malik; Raghbir Chand Gupta; Santosh Kumari; Akhtar Hussain Malik (The Scientific World Journal)
Presently Mertensia echioides Benth. (Boraginaceae) collected from Kashmir Himalaya, India, is cytologically analyzed for the first time revealing 2n=2x=24 (diploid). Interestingly we found 4.3–6.2% syncytic meiocytes/PMCs with 2n=4x=48 (tetraploid) in addition to normal meiocytes (2n=24) during male meiosis. These comparatively larger PMCs (pollen mother cells) lead to the formation of fertile giant 2n pollen grains. A frequency of 6.4–13.3% PMCs shows transfer of chromatin material at prophase-I and, therefore, results in aneuploid meiocytes. Whole chromatin transfer by the process of cytomixis could also have led to the formation of tetraploid cells. Translocation heterozygosity is also evident in the form of multivalents in 12–17% diploid (2x) meiocytes at diakinesis and metaphase-I and is reported for the first time in this species. The syncytes formed depict open chain hexavalent and quadrivalent formation in the three populations with different frequencies. Moreover chromatin stickiness at metaphase-I is observed in 45% of PMCs in population-1 (P-1). Syncyte or unreduced PMC formation leading to unreduced fertile gametes is here speculated to act as a possible way out for infraspecific polyploidization in the species.